2003
DOI: 10.1097/01.md.0000091185.93122.40
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Multicenter Study of Staphylococcus aureus Bacteremia

Abstract: Our objectives were to determine the incidence of endocarditis in patients whose Staphylococcus aureus bacteremia was community-acquired, related to hemodialysis, or hospital-acquired; to assess clinical factors that would reliably distinguished between S. aureus bacteremia and S. aureus endocarditis; to assess the emergence of methicillin-resistant S. aureus (MRSA) as a cause of endocarditis; and to examine risk factors for mortality in patients with S. aureus endocarditis. We conducted a prospective observat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
79
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 311 publications
(87 citation statements)
references
References 85 publications
7
79
0
1
Order By: Relevance
“…Previous observational studies have reported a similar mortality rate for SAB (15–40%) as in our study 2, 3, 4, 5, 6, 9, 10. However, the sources of bacteremia differed significantly between studies.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Previous observational studies have reported a similar mortality rate for SAB (15–40%) as in our study 2, 3, 4, 5, 6, 9, 10. However, the sources of bacteremia differed significantly between studies.…”
Section: Discussionsupporting
confidence: 78%
“…One observational study reported a similar rate of pneumonia (17/83, 21%)6 as that reported in the present study, but another study reported a lower rate of pneumonia (4/73, 5%) 7. In contrast, the studies of SAB that were undertaken outside of Japan generally reported a low rate of pneumonia 9, 10. A prospective observational study of SAB in the USA reported a low rate of respiratory tract infection (12/505, 2%) 9.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…While the importance of bactericidal therapy in the prompt eradication of bacteremia has been demonstrated, such analyses have not been done based on severity of host illness and on actual mortality. Since this was a retrospective cohort study, we did not have the means to measure duration of bacteremia but suspect that this effect on patient mortality by strains with agr dysfunction may lie in the longer duration of bacteremia, given the ample data linking duration of bacteremia to increased mortality and agr dysfunction to prolonged bacteremia (2,7). Testing for agr dysfunction may identify a subgroup of patients who need close vancomycin therapeutic monitoring or should receive other antistaphylococcal antibiotics.…”
Section: Discussionmentioning
confidence: 99%